ADVANCEMENT IN THE AGRICULTURE SECTOR USING IOT - et. al., Firdaus Khan (International Journal of Modern Agriculture, 2021)
The agriculture sector plays an important part in overcoming the food shortage situations for food security worldwide in the growing population scenario. In the agricultural sector, mechanization has increased different crop yield, opening a new age for achieving agricultural accuracy. Common use of farm machinery has recently been changed by modernizing agricultural machines. This breakthrough has been revolutionized by the field of precision farming. In the field of active irrigation, fungicides, fertilizers, and disease prevention in different plants, various types of high quality efficient sensors have been used. This strategy has raised agricultural production thus lowering production costs. In agriculture, the use of Internet of Things (IoT) technologies has helped farmers to relieve themselves by using smartphone apps and high-speed internet. These programmes provide information necessary for a farmer to manage a crop precisely by matching the data collected from a field with standard charts already contained in the database. In order to ensure accuracy in agriculture, this breakthrough in the automation of agricultural equipment also helps farmers to improve productivity, overcoming the world's food shortage. This paper reviews the advancement in the agricultural field by introducing IoT technology for the precision farming.